A CFD-DEM solver to model bubbly flow. Part I: Model development and assessment in upward vertical pipes. (2nd February 2018) - Peña-Monferrer, C.; Monrós-Andreu, G.; Chiva, S.; Martínez-Cuenca, R.; Muñoz-Cobo, J.L.
Graphical abstract: Highlights: Development of a CFD-DEM solver to model bubbly flow. Implementation of an equivolumetric subelement method. Development of a seeding algorithm in pipes and fluid flow influence investigation. Modeling of bubble expansion with a simplified model. Study of bubble dynamics and lateral forces related with turbulence and bubble size. Abstract: In the computational modeling of two-phase flow, many uncertainties are usually faced in simulations and validations with experiments. This has traditionally made it difficult to provide a general method to predict the two-phase flow characteristics for any geometry and condition, even for bubbly flow regimes. Thus, we focus our research on studying in depth the bubbly flow modeling and validation from a critical point of view. The conditions are intentionally limited to scenarios where coalescence and breakup can be neglected, to concentrate on the study of bubble dynamics and its interaction with the main fluid. This study required the development of a solver for bubbly flow with higher resolution level than TFM and a new methodology to obtain the data from the simulation. Part I shows the development of a solver based on the CFD-DEM formulation. The motion of each bubble is computed individually with this solver and aspects as inhomogeneity, nonlinearity of the interfacial forces, bubble-wall interactions and turbulence effects in interfacial forces are taken into account. To develop the solver, several features that are not usually required for traditional CFD-DEM simulations but are relevant for bubbly flow in pipes, have been included. Models for the assignment of void fraction into the grid, seeding of bubbles at the inlet, pressure change influence on the bubble size and turbulence effects on both phases have been assessed and compared with experiments for an upward vertical pipe scenario. Finally, the bubble path for bubbles of different size have been investigated and the interfacial forces analyzed.